Relationship of brand equity and innovation characteristics to acceptance and repurchase intention of smartphones - Wong, Chee Hoo (2012)
This study examined the major factors that contributed towards Acceptance and Repurchase Intention of smartphone among working executives in Malaysia. It too evaluates the direct and indirect effect of Acceptance on Repurchase Intention. In short, the main objective of this study was to examine the relationship between brand equity, innovation characteristics, acceptance, and repurchase intention. Using Theory of Reasoned Action, Innovation Diffusion Theory and Brand Equity Model, a quantitative research was carried out to achieve the research objectives. The survey was to establish that Brand Equity dimensions and Innovation Characteristics had significant influence on Acceptance, while Brand Equity and Innovation Characteristics directly affect Repurchase Intention. Cluster sampling was chosen where the questionnaires were distributed to 600 samples in Malaysia with emphasis on major smartphone penetration areas in Selangor and Federal Territory Kuala Lumpur. The study uses Structural Equation Modeling (SEM) to test the significance of the overall model and the specified paths. The findings of the research demonstrated three main results. First, Innovation Characteristics (via Relative Advantage, Compatibility and Image) significantly influenced Acceptance of smartphone. Second, this research also pointed that Brand Equity (via Brand Awareness), Innovation Characteristic (via Result Demonstrability, Image and Voluntariness), and Acceptance significantly influenced Repurchase Intention. Third, the findings indicated that Acceptance significantly mediates the relationship between Innovation Characteristics (via Image) and Repurchase Intention. In addition, the study showed that Innovation Characteristics was important for Acceptance of Smartphone. After the consumer had adopted smartphone, the role of Brand Equity becomes important. In essence, it plays significant role together with Innovation Characteristics and Acceptance in determining Repurchase Intention of Smartphone. At the same time, Acceptance too asserts significant mediating influence in the relationship between Innovation Characteristics and Repurchase Intention. Acceptance had successfully mediates the relationship between Image and Repurchase Intention. In conclusion, the results implied that, smartphone Acceptance was influenced by consumers’ utilitarian values, while Repurchase Intentions were influenced by utilitarian and hedonic values. The result also stressed a point that getting Acceptance also helps in increasing the Repurchase Intention level.